Gender, Sustainability, and Behavior : A TPB Analysis of Eastern India’s Green Purchases - Majumder, Jayeeta; Gangopadhyay, Sourav; Biswas, Susmi (Prabandhan: Indian Journal of Management, 2025)
Purpose : This study examined how gender influences green product purchasing behavior, focusing on gender’s moderating role in purchase intention. The aim was to understand whether gender-based differences in consumer behavior could contribute to promoting sustainability and addressing environmental concerns. Design/Methodology/Approach : The study used a multigroup structural equation modeling method to assess data collected from 306 respondents using a self-administered and structured questionnaire. The theory of planned behavior (TPB) was the conceptual model, and it included perceived behavioral control, subjective norms, environmental knowledge, attitude, and environmental concern as indicators of actual behavior and purchase intention. Findings : The findings highlighted that gender significantly affected green purchasing. When it came to green purchases, purchase intention substantially impacted the actual behavior of females. The effect of attitude and environmental concerns on purchase intention for females was significant, but not for males. Subjective norms and environmental knowledge showed a considerable but insignificant impact on females. Perceived behavioral control had an insignificant effect on either group. Gender moderated several key relationships within the model, indicating different behavioral pathways for male and female consumers. Practical Implications : The investigation offered information for marketers and policymakers by highlighting the need for gender-sensitive strategies to promote green products. Tailoring messages to align with gender-specific motivations may enhance consumer engagement in sustainable consumption. Originality/Value : The present research extended the TPB and provided empirical information concerning the gendered dynamics of green purchasing behavior, contributing to academic literature and practical sustainability initiatives.